On Legal Personhood of Artificial Intelligence - Miščević, Nikolina B.; Savčić, Sanja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Artificial intelligence is becoming an increasingly significant factor in social and economic life. As it is capable of performing a large portion of tasks as well as or even better and faster than humans, its use is becoming widespread, ranging from simple tasks in manufacturing plants to participating in online conclusion of contract and even in diagnostics and surgical procedures in medicine. Although it represents a huge potential for progress and development in society and the improvement of quality of life of an individual, it also brings significant risks. The question of the legal personhood of artificial intelligence was raised long before it became such a significant factor in legal transactions. However, in the last decade, it has become particularly relevant. Despite this, there is disagreement in the doctrine, both in terms of terminology and regarding whether artificial intelligence should be recognized as a legal subject or not. The paper presents various arguments on which authors advocating for the recognition of legal personhood of AI have based their stance, as well as reasons on which other authors base their skepticism towards expanding the circle of legal subjects in favor of artificial intelligence. At the end of the paper, based on the analysis of the presented views and arguments, the authors take a stance on whether and under what conditions legal personhood should be recognized to artificial intelligence.